Supply Chain Management Strategies in Project and Absorptive Capacity to Implementation Partnership Strategy in New Product Development - Gheshmi, Reza; Zarco, Hugo; Marimon, Frederic (ExcelingTech, 2019)
To develop new and successful products, supply chain management can be efficient way as a multidisciplinary process. It appears logical to consider that some elements, such as fast changes in technology, a flexible process of production, and international rivalry, have a direct relationship across various knowledge sources and are more necessary for introducing timely and profitable new products. Our main emphasis is to make a comparative assessment forthe role of decomposed attributes of complexity level in new project development (NPD) and internal abilities to choose partnership as dominant mode for external collaboration in different phases of NPD, by using supply chain management design across 125 NPD projects in low technology-intensive SMEs in Spain. The results provide support for the role of absorptive capacity and different dimensions of project complexity in developing a co-development strategy (Partnership) in different phases of NPD projects.